Electrode for producing hydrogen by electrolyzing water and preparation method thereof
Through one-step aluminizing method and micro-dealloy treatment, ultra-thin microporous structure is constructed on the surface of the nickel-based electrode, which solves the problems of low catalytic performance and high production cost of the existing electrolytic hydrogen production electrode, and achieves high efficiency and low energy consumption hydrogen precipitation, which is suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202411641334.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing electrolytic water-based hydrogen production electrode has low catalytic performance, low efficiency, high energy consumption, and high production cost of nickel-based catalysts, making it difficult to adapt to large-scale industrial applications.
A one-step aluminizing method combined with micro-dealloy treatment was used to construct an ultra-thin microporous structured micro-dealloy layer on the surface of the nickel-based substrate, and the process parameters were regulated to improve the specific surface area and active sites, and to optimize mass transfer kinetics and electron transport.
It significantly improves the electrocatalytic performance of the electrode, reduces the energy barrier of the hydrogen evolution reaction, improves the utilization rate and production efficiency of the material, ensures the long-term stability and durability of the electrode, and is suitable for large-scale industrial production.
Smart Images

Figure CN119506948A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical catalysis, and in particular relates to an electrode for producing hydrogen by electrolyzing water and a preparation method thereof. Background Art
[0002] In recent years, with the development of human society, environmental problems have become increasingly severe, and the threat of resource depletion has become increasingly imminent. Against this background and the goal of carbon neutrality, clean renewable energy has attracted widespread attention, and hydrogen energy is considered to be one of the most ideal clean energy sources due to its abundant reserves, clean and environmentally friendly, high combustion calorific value, and secondary renewable advantages. At present, there are three main ways to produce hydrogen in industry: coal gasification, methane reforming, and water electrolysis, which correspond to gray hydrogen, blue hydrogen, and green hydrogen, respectively. However, CO2 and other pollutants will be produced during the preparation of gray hydrogen and blue hydrogen, which will inevitably cause damage to the environment. Water electrolysis has abundant raw materials, environmentally friendly products, and high purity hydrogen. However, it is also limited by factors such as low efficiency and high energy consumption, resulting in high hydrogen production costs, which in turn limits the further expansion of its industrial application scale. Therefore, it is particularly important to develop high-performance and low-cost catalysts to reduce overpotential and thus reduce energy consumption. Pt-based catalysts are still catalysts with very superior performance. However, due to their scarce reserves, high prices, and stability issues, they have not been widely used. Nickel and its alloy mesh are still the main ones used in industry. However, the catalytic performance of industrial nickel mesh is still significantly different from that of precious metal-based catalysts. Therefore, further improving and improving the catalytic performance of nickel mesh is of great practical significance. The improvement of catalytic performance is mainly divided into two directions: one is to increase the specific surface area and expose more active sites; the other is to improve its intrinsic activity. A large number of studies have shown that porous structures can greatly increase the specific surface area of catalytic materials, thereby achieving the effect of improving catalytic effects and reducing overpotentials. Raney nickel is a typical highly porous nickel-based material with good catalytic effects. However, most of the Raney nickel currently produced is in powder form and needs to be attached to the substrate material for a second time, which brings a series of problems, such as large interface mass transfer resistance, high charge transfer impedance, and a sharp drop in catalytic performance caused by powder shedding after long-term operation. In the existing reports, only a few studies have constructed a porous structure layer similar to Raney nickel on the surface of sheet or block nickel-based metal for water electrolysis catalysis. However, its thickness is basically more than tens of microns. On the one hand, too thick a catalytic layer will affect mass transfer and bubble desorption, and on the other hand, it will significantly increase the material cost. In addition, these documents all prepare the nickel-aluminum alloy layer by physical vapor deposition / electrochemical deposition and subsequent heat treatment. The preparation cost is high, the deposition uniformity cannot be guaranteed, and it is not suitable for large-scale industrial production.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide an electrode for producing hydrogen by electrolysis of water and a preparation method thereof, and solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0006] A method for preparing an electrode for producing hydrogen by electrolyzing water comprises the following steps:
[0007] Step (1) taking aluminum powder, ammonium chloride and aluminum oxide, putting them into a mortar and grinding them, and obtaining mixed aluminum powder after the powders are evenly mixed;
[0008] Step (2) selecting a nickel-based material as a substrate, then ultrasonically cleaning the nickel-based material using hydrochloric acid, acetone, ethanol and deionized water in sequence, and placing the nickel-based material in a vacuum oven for drying after the cleaning is completed;
[0009] Step (3) burying the dried nickel-based substrate in the mixed aluminized powder, sealing it in a crucible, heating and keeping it warm under argon protection to combine the aluminized powder with the nickel-based substrate, and after cooling to room temperature, obtaining an aluminized nickel mesh;
[0010] Step (4) using acetone, ethanol and deionized water to ultrasonically clean the aluminum-nickel mesh, and then drying it in a vacuum drying oven;
[0011] Step (5) placing the dried aluminized nickel mesh in a mixed solution of sodium hydroxide or potassium hydroxide or potassium sodium tartrate tetrahydrate and potassium hydroxide, and heating and heat preservation in a water bath to form a surface porous structure;
[0012] Step (6) The treated electrode is rinsed with deionized water until the pH value is neutral, and then placed in a vacuum oven to dry, thereby completing the preparation of the water electrolysis hydrogen production electrode.
[0013] It should be noted that the present invention successfully constructs an ultra-thin micro-dealloyed layer on the surface of the nickel-based substrate by regulating the process parameters. The thickness of this layered porous structure is much smaller than that of the traditional dealloyed layer, and the pore distribution is more uniform, which greatly improves the specific surface area and the number of active sites of the electrode, and increases the active area in the electrocatalytic reaction. Compared with the conventional dealloyed structure, the micro-dealloyed layer significantly optimizes the mass transfer kinetics, reduces the mass transfer resistance during the reaction process, and increases the electron transfer rate inside and outside the electrode, thereby effectively improving the electrocatalytic performance of the material. In addition, this microstructure is closely integrated with the substrate material, which enhances the stability of the electrode in long-term cyclic use and reduces the risk of surface shedding. At the same time, this technology relies on simple, low-cost process steps, making the production process more economical, avoiding the high energy consumption and high cost problems of traditional complex processes, and laying the foundation for large-scale industrial production.
[0014] Optionally, the composition of the aluminized powder in step (1) is 1-10wt% aluminum powder, 3wt% NH4Cl powder and the balance of Al2O3 powder, and the time for grinding the powder in the mortar in step (1) is 5-15 minutes.
[0015] Optionally, the nickel-based substrate in step (2) includes one of nickel and nickel-based alloy sheets, nickel and nickel-based alloy meshes, and nickel and nickel-based alloy foams. The ultrasonic cleaning time in step (2) is 5-15 minutes, the oven temperature during drying is 40-70°C, and the drying time is 0.5-3 hours.
[0016] Optionally, the aluminizing process in step (3) is carried out at 750-1000° C. and kept warm for 1-6 hours.
[0017] Optionally, in step (4), the ultrasonic cleaning time of the aluminum-nickel mesh is 0.5-2 hours, the drying temperature is 40-70° C., and the drying time is 0.5-3 hours.
[0018] Optionally, the dealloying process in step (5) is carried out in a water bath at 60-100° C. for 1-24 hours.
[0019] Optionally, the drying in step (6) is performed in a vacuum oven at 40-70° C. for 0.5-3 hours.
[0020] A water electrolysis hydrogen production electrode prepared by the method for preparing a water electrolysis hydrogen production electrode.
[0021] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0022] 1. The present invention adopts a one-step aluminizing method combined with a micro-dealloying treatment, and constructs a micro-dealloying layer with an ultra-thin microporous structure on the surface of the nickel-based substrate by controlling the ratio of aluminizing powder, aluminizing temperature and time, and key process parameters such as the composition and treatment time of the dealloying solution. This micro-dealloying layer has a smaller thickness and a more uniform pore distribution. Compared with the traditional dealloying structure, it not only significantly increases the specific surface area and active sites, but also effectively optimizes the mass transfer kinetics and electron transmission path, and reduces the energy barrier in the hydrogen evolution reaction process.
[0023] 2. The process of the present invention improves the utilization rate of materials, reduces the amount of catalyst used and the production cost, making it more suitable for large-scale industrial applications. It is worth mentioning that the bonding force between the catalyst layer of the present invention and the nickel-based substrate is significantly enhanced, avoiding the risk of surface layer shedding during long-term use, and ensuring the long-term stability and durability of the electrode. These advantages make the electrode prepared by the present invention superior to traditional dealloying catalysts in terms of cycle performance, catalytic efficiency and economy.
[0024] 3. The process for preparing the nickel-based electrode for producing hydrogen by electrolyzing water with surface micro-dealloying of the present invention is simple and low in cost. The related basic technology used in the decomposition step is relatively mature in the industry and only needs to be slightly changed and adjusted based on the existing industrial conditions, which is conducive to industrial large-scale preparation.
[0025] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0027] In the figure:
[0028] Figure 1 The cross-sectional SEM and linear scanning images of the optimal sample prepared in the present invention.
[0029] Figure 2 This is the surface SEM image of the optimal sample prepared in the present invention.
[0030] Figure 3 This is the HER-LSV diagram of the optimal sample prepared by the present invention.
[0031] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] See also Figure 1-3 As shown, in this embodiment, a method for preparing an electrode for producing hydrogen by electrolysis of water is provided, comprising the following steps:
[0038] Step (1) taking aluminum powder, ammonium chloride and aluminum oxide, putting them into a mortar and grinding them, and obtaining mixed aluminum powder after the powders are evenly mixed;
[0039] Step (2) selecting a nickel-based material as a substrate, then ultrasonically cleaning the nickel-based material using hydrochloric acid, acetone, ethanol and deionized water in sequence, and placing the nickel-based material in a vacuum oven for drying after the cleaning is completed;
[0040] Step (3) burying the dried nickel-based substrate in the mixed aluminized powder, sealing it in a crucible, heating and keeping it warm under argon protection to combine the aluminized powder with the nickel-based substrate, and after cooling to room temperature, obtaining an aluminized nickel mesh;
[0041] Step (4) using acetone, ethanol and deionized water to ultrasonically clean the aluminum-nickel mesh, and then drying it in a vacuum drying oven;
[0042] Step (5) placing the dried aluminized nickel mesh in a mixed solution of sodium hydroxide or potassium hydroxide or potassium sodium tartrate tetrahydrate and potassium hydroxide, and heating and heat preservation in a water bath to form a surface porous structure;
[0043] Step (6) The treated electrode is rinsed with deionized water until the pH value is neutral, and then placed in a vacuum oven to dry, thereby completing the preparation of the water electrolysis hydrogen production electrode.
[0044] In the following examples, the composition of the aluminized powder in step (1) is 1-10wt% aluminum powder, 3wt% NH4Cl powder and the balance of Al2O3 powder, and the time for grinding the powder in the mortar in step (1) is 5-15 minutes.
[0045] In the following embodiments, the nickel-based substrate in step (2) comprises one of nickel and nickel-based alloy sheets, nickel and nickel-based alloy meshes, and nickel and nickel-based alloy foams. The ultrasonic cleaning time in step (2) is 5-15 minutes, the oven temperature during drying is 40-70° C., and the drying time is 0.5-3 hours.
[0046] In the following examples, the aluminizing process in step (3) is carried out at 750-1000° C. and kept warm for 1-6 hours.
[0047] In the following examples, the ultrasonic cleaning time of the aluminum-nickel mesh in step (4) is 0.5-2 hours, the drying temperature is 40-70° C., and the drying time is 0.5-3 hours.
[0048] In the following examples, the dealloying process in step (5) is carried out in a water bath at 60-100° C. for 1-24 hours.
[0049] In the following examples, the drying step (6) is performed in a vacuum oven at 40-70°C for 0.5-3 hours.
[0050] The present invention will now be further described in detail with reference to embodiments.
[0051] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.
[0052] Embodiment 1: This embodiment provides a method for preparing an electrode for producing hydrogen by electrolysis of water, comprising the following steps:
[0053] Step (1) 10% aluminum powder, 3% ammonium chloride and 87% aluminum oxide powder are weighed and placed in a mortar, ground for 10 minutes, and mixed evenly to obtain a mixed aluminized powder;
[0054] Step (2) Select a nickel mesh as the substrate material. Use hydrochloric acid, acetone, ethanol and deionized water to ultrasonically clean the nickel mesh for 10 minutes in sequence to remove impurities and contaminants on the surface. After cleaning, place the nickel mesh in a vacuum oven and dry it at 60°C for 1 hour;
[0055] Step (3) The dried nickel mesh is completely buried in the mixed aluminized powder, placed in a crucible and sealed. In an argon protective atmosphere, the crucible is placed in a tube furnace and heated to 950°C for 5 hours to allow the aluminum and the nickel mesh to fully react and form an alloy layer. After cooling to room temperature, an aluminized nickel mesh is obtained;
[0056] Step (4) The cooled aluminized nickel mesh is ultrasonically cleaned with acetone, ethanol and deionized water for 1 hour in sequence to remove surface residues. After cleaning, the aluminized nickel mesh is placed in a vacuum drying oven and dried at 60° C. for 1 hour to prepare for dealloying;
[0057] Step (5) placing the dried nickel mesh in a 5 mol / L sodium hydroxide solution and heating it in a water bath at 80° C. for 2 hours to form a porous structure on the surface of the nickel mesh;
[0058] Step (6) The dealloyed electrode is rinsed with deionized water until the pH value is neutral to remove the residual alkali solution. Subsequently, the electrode is placed in a vacuum oven and dried at 60° C. for 1 hour to complete the preparation of the water electrolysis hydrogen production electrode.
[0059] Embodiment 2: This embodiment provides a method for preparing an electrode for producing hydrogen by electrolysis of water, comprising the following steps:
[0060] In order to explore the effect of the aluminum powder content in the aluminized powder on the electrode performance, the mass fraction of the aluminum powder in step (1) of Example 1 was replaced with 1%, 3% and 5% respectively. The remaining steps were the same as in Example 1.
[0061] Embodiment 3: This embodiment provides a method for preparing an electrode for producing hydrogen by electrolysis of water, comprising the following steps:
[0062] In order to explore the effect of the holding temperature in the aluminizing step on the electrode performance, the holding temperatures in step (3) of Example 1 were replaced with 750° C. and 850° C. respectively. The other steps were the same as in Example 1.
[0063] Embodiment 4: This embodiment provides a method for preparing an electrode for producing hydrogen by electrolysis of water, comprising the following steps:
[0064] In order to explore the effect of the holding time in the aluminizing step on the electrode performance, the holding time in step (3) in Example 1 was replaced with 1 hour and 3 hours respectively. The other steps were the same as in Example 1.
[0065] Embodiment 5: This embodiment provides a method for preparing an electrode for producing hydrogen by electrolysis of water, comprising the following steps:
[0066] In order to explore the effect of the solution formula in the dealloying step on the electrode performance, the dealloying solution in step (5) of Example 1 was replaced with potassium hydroxide (KOH) and a mixed solution of potassium sodium tartrate tetrahydrate and potassium hydroxide. The remaining steps were the same as in Example 1.
[0067] Embodiment 6: This embodiment provides a method for preparing an electrode for producing hydrogen by electrolysis of water, comprising the following steps:
[0068] In order to explore the effect of the dealloying time in the dealloying step on the prepared electrode, the dealloying time in step (5) of Example 1 was replaced with 6 hours and 12 hours. The other steps were the same as in Example 1.
[0069] Test example 1: Cross-sectional SEM and linear scanning image test of the optimal sample
[0070] During the test, the optimal sample is first prepared into a cross-sectional sample, fixed on the sample stage, and electron beam scanning is performed using a scanning electron microscope (SEM) under high vacuum conditions. At the same time, energy dispersive spectroscopy (EDS) linear scanning is performed along the cross section to obtain element distribution maps and cross-sectional microstructure images.
[0071] Depend on Figure 1 It can be seen that the thickness of the micro-dealloyed layer is about 5 microns, and the layer structure shows good continuity and uniformity. A significant increase in the aluminum content was detected near the center of the cross section, which was mainly caused by the adhesion of surface debris during the sample preparation process. These debris may come from the mechanical cutting of the sample or tiny particles remaining during the preparation process, which interferes with the elemental analysis of the local area. This shows that in the future sample preparation process, the cutting and cleaning steps need to be more strictly controlled to avoid composition determination errors caused by debris adhesion, thereby ensuring the accuracy of the analysis results.
[0072] Test example 2: Surface SEM image test of the optimal sample
[0073] When using a scanning electron microscope (SEM) to characterize the surface microstructure during testing, first fix the sample on the sample stage and ensure that the surface is clean and dry. Then, scan the sample with an electron beam in a high vacuum environment, adjust the acceleration voltage and magnification, and record and save the microscopic image of the sample surface.
[0074] Depend on Figure 2It can be seen that the surface presents a distinct porous morphology, and these holes are evenly distributed on the electrode surface, forming a complex microstructure. This porous structure not only significantly increases the specific surface area of the electrode, but also provides more active sites for electrochemical reactions, which helps to improve the efficiency of electron transfer. In addition, the porous morphology can also optimize the generation and desorption process of bubbles and reduce the obstacles caused by gas retention during the reaction. The formation of this microstructure shows that during the dealloying and surface treatment process, the process is properly controlled to ensure the uniform pore distribution on the electrode surface, laying the foundation for improving its electrocatalytic performance.
[0075] Test Example 3: Electrocatalytic performance of electrode materials in water electrolysis
[0076] During the test, a three-electrode system was built in a 1M KOH solution, using a surface micro-dealloyed nickel mesh as the working electrode, a carbon rod as the counter electrode, and a Hg / HgO electrode as the reference electrode. Before the experiment, the working electrode was pretreated by multiple cyclic voltammetry scans to activate the surface. Then, linear sweep voltammetry (LSV) was used to record the curve of current density versus potential in the potential range of -0.6V to 0V at a scan rate of 5-10mV / s. The current density obtained in the curve reached 10mA / cm -2 The overpotentials of different electrodes were compared to evaluate the performance of hydrogen evolution reaction. Figure 3 shown.
[0077] Depend on Figure 3 It can be seen that at a current density of 10 mA cm -2 When the overpotential of the surface micro-dealloyed nickel mesh prepared by the present invention is only 51mV, which is significantly better than the 86mV of the commercial sprayed Raney nickel mesh and the 266mV of the commercial pure nickel mesh. This result shows that the electrode of the present invention has a higher electrochemical catalytic efficiency, and the surface micro-dealloying treatment effectively reduces the energy barrier of the hydrogen evolution reaction. This lower overpotential indicates that the electrode can achieve efficient hydrogen evolution at a lower potential, reducing energy consumption. In addition, the curve shows that the electrode of the present invention can also maintain good stability within a larger current density range, showing its great potential in industrial water electrolysis applications. These results highlight the advantages of the surface micro-dealloyed layer, that is, by increasing active sites, optimizing mass transfer paths and electron transfer rates, the electrocatalytic performance is significantly improved.
[0078] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A method for preparing an electrode for producing hydrogen by electrolysis of water, characterized in that: The following steps are involved: Step (1) taking aluminum powder, ammonium chloride and aluminum oxide, putting them into a mortar and grinding them, and obtaining mixed aluminum powder after the powders are evenly mixed; Step (2) selecting a nickel-based material as a substrate, then ultrasonically cleaning the nickel-based material using hydrochloric acid, acetone, ethanol and deionized water in sequence, and placing the nickel-based material in a vacuum oven for drying after the cleaning is completed; Step (3) burying the dried nickel-based substrate in the mixed aluminized powder, sealing it in a crucible, heating and keeping it warm under argon protection to combine the aluminized powder with the nickel-based substrate, and after cooling to room temperature, obtaining an aluminized nickel mesh; Step (4) using acetone, ethanol and deionized water to ultrasonically clean the aluminum-nickel mesh, and then drying it in a vacuum drying oven; Step (5) placing the dried aluminized nickel mesh in a mixed solution of sodium hydroxide or potassium hydroxide or potassium sodium tartrate tetrahydrate and potassium hydroxide, and heating and heat preservation in a water bath to form a surface porous structure; Step (6) The treated electrode is rinsed with deionized water until the pH value is neutral, and then placed in a vacuum oven to dry, thereby completing the preparation of the water electrolysis hydrogen production electrode.
2. The method for preparing a water electrolysis hydrogen production electrode according to claim 1, characterized in that: The composition of the aluminized powder in step (1) is 1-10wt% aluminum powder, 3wt% NH4Cl powder and the balance of Al2O3 powder. The time for grinding the powder in a mortar in step (1) is 5-15 minutes.
3. The method for preparing a water electrolysis hydrogen production electrode according to claim 1, characterized in that: The nickel-based substrate in step (2) includes one of nickel and nickel-based alloy sheets, nickel and nickel-based alloy meshes, and nickel and nickel-based alloy foams. The ultrasonic cleaning time in step (2) is 5-15 minutes, the oven temperature during drying is 40-70° C., and the drying time is 0.5-3 hours.
4. The method for preparing a water electrolysis hydrogen production electrode according to claim 1, characterized in that: In step (3), the aluminizing process is carried out at 750-1000° C. and kept warm for 1-6 hours.
5. The method for preparing a water electrolysis hydrogen production electrode according to claim 1, characterized in that: In step (4), the ultrasonic cleaning time of the aluminum-nickel mesh is 0.5-2 hours, the drying temperature is 40-70° C., and the drying time is 0.5-3 hours.
6. The method for preparing a water electrolysis hydrogen production electrode according to claim 1, characterized in that: The dealloying process in step (5) is carried out in a water bath at 60-100° C. for 1-24 hours.
7. The method for preparing a water electrolysis hydrogen production electrode according to claim 1, characterized in that: The drying step (6) is carried out in a vacuum oven at 40-70°C for 0.5-3 hours.
8. An electrode for producing hydrogen by electrolysis of water prepared by the method for preparing an electrode for producing hydrogen by electrolysis of water according to any one of claims 1 to 7.